A 3D peridynamic fluid–solid coupling damage model of hydraulic fracture propagation. Issue 1 (19th October 2022) - Li, Yalong; Hu, Zhiming; Qiu, Zhipeng; Qiu, Yafeng
Abstract: Peridynamics provides a new model and method for describing material failure and fracture development. In this study, a three‐dimensional peridynamic fluid–solid coupling model of hydraulic fracture propagation was established. The model considered the effective stress and transverse isotropic characteristics of shale and was used to simulate the propagation of the hydraulic fracturing of bedding shale. The damage evolution influence on the fracture propagation behavior, as well as the interactions between the fractures and bedding, were investigated through a simulation. The damage evolution had discontinuous characteristics. In addition to the incomplete damage zone adjacent to the complete damage zone, there were nonadjacent and incomplete damage zones. The fracture and propagation of hydraulic fractures followed the same trends of damage evolution. Moreover, the simulation and related experimental results confirmed the existence of a large amount of mesodamage in the region far from the fracture, and the concept of "remote damage" in hydraulic fracturing was proposed. Finally, the damage evolution of the propagating fractures and bedding was simulated. The simulation showed that bedding hinders the propagation of main fractures in the height direction but promotes the complexity of fracture propagation. Overall, this study provides a new theoretical understanding and research ideas for an in‐depth understanding of hydraulic fracture geometry and the accurate calculation of Stimulated Reservoir Volume. Abstract : Considering the transverse isotropy of shale, a three‐dimensional (3D) peridynamic fluid–solid coupling model of hydraulic fracture propagation is established. The 3D fracture propagation dynamics of bedding shale were simulated.